Class Wide Peer Tutoring (Cwpt) Strategy: Its Impact to Students’ Readin Comprehension of Grade Eight Students of SMP 1 Sungai Rumbai Dharmasraya - Rauldatul Husni (Universitas PGRI Semarang, 2018)
Class Wide Peer Tutoring (CWPT) Strategy is chosen to be applied in order to develop the teacher’s strategy in teaching learning process especially Narrative Text. The objective of the research is to examine whether or not Class Wide Peer Tutoring (CWPT) Strategy can improve students’ Reading Comprehension of grade eight students of SMP 1 Sungai Rumbai Dharmasraya. Besides, the researcher is also designed to study what happens when Class Wide Peer Tutoring (CWPT) Strategy applied.To get the data in this research, the researcher used test as an instrument. The researcher gave them multiple choice, to know how well the students already mastered reading comprehension on narrative text. The data of the research were collected in three steps as stated, Pre-test. The researcher gave pret-test to the control and experimental groups in order to know students reading comprehension level and to cover students score in mastering reading comprehension. Than treatment, The researcher prepared materials by giving treatment using CWPT in teaching narrative text for experimental group focused on reading comprehension and Questioning strategy for control group in order to compare both of the strategy given. The last Post-test. The researcher gave post-test to experimental group and control group after giving the treatment. After gathering the data, the researcher analyzed the students’ result by using a statistical formula which is called t-test. The researcher calculated the significant differences for Class Wide Peer Tutoring. By using CWPT strategy the teacher can increase students ability in reading comprehensin. The finding reveal that Class Wide Peer Tutoring (CWPT) strategy can improve students’ reading comprehension, where students work in pair, help each other to accomplish individual and pair task. Furthermore, in CWPT strategy the teacher guides the students in pair activities, provides feedback on pair fuctioning and intervenes when necessary. Class Wide Peer Tutoring (CWPT) Strategy as used in this research gave good Impact to students’ Reading Comprehension, especially in narrative text of SMP 1 Grade Eight students Sungai Rumbai Dharmasraya. The use of this strategy helped the students comprehend the text, made the students participate actively in the learning process, gave good response during pairing activity, and provided fun which facilitated more learning.